PENGARUH VARIASI MUTU JAKET BETON DAN PENAMBAHAN TULANGAN LATERAL TERHADAP KAPASITAS AKSIAL KOLOM BUJUR SANGKAR - Dharma Giri, Ida Bagus (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021, 2021)
Many researches have been carried out regarding concrete jacketing, such as the addition of stirrup reinforcement and enlargement of dimensions with the quality of the concrete jacket that is equal or exceeds the quality of the core column concrete. To determine the effect of concrete jacket quality and the addition of stirrup reinforcement to the axial column capacity, in this study, the core column (K25) with 25 MPa quality and the quality of the concrete jacket varied 20 MPa, 25 MPa, 30 MPa, with the addition of stirrup reinforcement (KJs column) and without the addition of stirrup reinforcement (KJ column) in each variation of the quality of concrete jackets. It made 3 colomn for each type of treatment. The core column has a square shape with dimensions 80 x 80 x 320 mm and a concrete reinforcement jacket is given with dimensions 160 x 160 x 300 mm. The column is given concentric axial load and the shortening is calculated using a dial gauge for every 20 kN load. The results of this study indicate the addition of jacket and stirrup reinforcement concrete can increase axial capacity and column ductility. As for the increase in axial capacity that occurs in the KJ20, KJ25, KJ30 column, the K25 column is respectively 17.4%; 34.0%; 34.7%. While the axial capacity increase in the KJs20, KJs25, KJs30 columns, for the K25 column is 54.9%; 62.5%; 71.5%. The reinforcement column with the addition of stirrup reinforcement, has a shorter value and greater axial capacity than the core column and reinforcement column without accompanying the addition of stirrups. The increase in axial capacity that occurs also increases along with the increase in the concrete compressive strength of the jacket which is used as reinforcement.   Keywords : quality variation, axial capacity, concrete jacketing.